Gender Discrimination, Disability and Legal Reforms: Revisiting the Evidence - Roy, Subir Kumar (Brawijaya Law Journal, 2020)
This article intends to discuss how gender affects women’s and men’s experience of disability and their basic human rights. It discusses at length about the Feminist Disability Study and its relation with the feminist study to find out a clear conception about the gender disability. This article arduously searches whether the Issues of disability has any linkage with the theory of right and exclusions or it is a kind of cultural interpretation of human variation. Disabled woman suffers double discrimination which is quite different from the experiences of a disabled man. This article intends to critically scan the whole International legal mechanism and the Indian legal system relating to the disability of women and also suggests how to improve the situation. The approach of the article is primarily doctrinal based on an analysis of comparative legal structure, policies, governmental documents, judicial pronouncements, etc. This article advocates in favour of collaborative governance to address the issue of Women’s disability properly.